Analisis Sitem Pengendalian Intern Kas pada PT Pelabuhan Indonesia I (Persero) Medan - Wasih Latuh Rahmi (Economic Reviews Journal, 2023)
Cash is referred to as the most liquid property and is a component of current assets which include banknotes / metals and other objects that can be used as a legal and retrievable medium of exchange every time. If the cash inventory is sufficient, the company will operate smoothly, especially in cash expenditure activities which include the purchase of goods and services, and therefore in order for the company to avoid misappropriation, the cash is used as well as possible. Cash is inseparable from receiving and payment activities. The purpose of this study is to describe how the Cash Internal Control System and analyze the Cash Internal Control System in the company of PT. Port of Indonesia I (Persero) Medan. The internal cash control system is a control system that is able to protect the company's cash, and keep away from losses due to intentional or unintentional mistakes. The internal control system is divided into two systems, namely cash receipts and expenditures. In this study, the problem arises because of the sequence number of the evidence that is not printed and does not have a stamp stamp "FULL" on the cash evidence that has been paid. The research approach that the author uses is a descriptive research approach. The type of data collected to support the variables studied is a qualitative data type. The data sources used are primary data and secondary data. The data collection techniques used are the interview method and documentation method. The data analysis technique in this study uses a descriptive analysis method. Based on the results of the analysis by comparing the cash internal control system at PT. Port of Indonesia I (Persero) Medan with elements of the COSO model internal control system, cash internal control system at PT. Port of Indonesia 1 (Persero) Medan has not yet reached the goal of the internal control system. This is because there are several elements of the internal cash control system in the company that still have weaknesses. Keywords: Cash, Internal Control System, Cash Internal Control System